2014
DOI: 10.1210/jc.2013-1569
|View full text |Cite
|
Sign up to set email alerts
|

Increasing LH Pulsatility in Women With Hypothalamic Amenorrhoea Using Intravenous Infusion of Kisspeptin-54

Abstract: Background:Hypothalamic amenorrhea (HA) is the one of the most common causes of period loss in women of reproductive age and is associated with deficient LH pulsatility. High-dose kisspeptin-54 acutely stimulates LH secretion in women with HA, but chronic administration causes desensitization. GnRH has paradoxical effects on reproductive activity; we therefore hypothesized that a dose-dependent therapeutic window exists within which kisspeptin treatment restores the GnRH/LH pulsatility in women with HA.Aim:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 50 publications
3
88
0
3
Order By: Relevance
“…Our findings have pharmacological and potential therapeutic relevance as the plasma kisspeptin levels achieved in this study, which enhanced GSIS, are similar to those required to restore LH pulsatility in women with hypothalamic amenorrhea3 and trigger oocyte maturation in in vitro fertilisation protocols 2. During IVGTTs, pharmacological kisspeptin administration increased insulin secretion and increased disposition index (IVGTT‐DI).…”
Section: Discussionsupporting
confidence: 66%
“…Our findings have pharmacological and potential therapeutic relevance as the plasma kisspeptin levels achieved in this study, which enhanced GSIS, are similar to those required to restore LH pulsatility in women with hypothalamic amenorrhea3 and trigger oocyte maturation in in vitro fertilisation protocols 2. During IVGTTs, pharmacological kisspeptin administration increased insulin secretion and increased disposition index (IVGTT‐DI).…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, in women with HA, desensitisation was observed after continuous SC administration of Kp-54 for two weeks [106], but the evidence is not consistent in other studies [1]. Recently in a study in women having HA, eight hours infusion of low dose Kp-54 restored pulsatile release of LH in addition to continuous LH secretion [59], and in another study in healthy women, their menstrual cycle was advanced by continuous administration of Kp-54 [94]. The studies done in healthy men showed varied results with no evidence of desensitisation to continuous infusion of Kp-10 at lower dose while LH response was reduced when continuous infusion of high dose Kp-10 was given for 24 hours [1,57].…”
Section: Continuous Kisspeptin Exposure Leads To Desensitisationmentioning
confidence: 84%
“…There was sustained gonadotrophins secretion over the eight weeks period although the response was reduced in the later period compared to day 1 and it again did not result in significant oestradiol release and ovulation was not achieved [107]. Furthermore, it has been shown recently that LH pulsatility could be achieved after Kp-54 infusion for eight hours with a three-fold rise in LH pulse frequency and mass per pulse [59], which supports the hypothesis that in order to restore reproductive endocrine activity in females with HA, pulsatile delivery of kisspeptins should be given because kisspeptin release is pulsatile [54,108]. This is similar to the fact that in order to stimulate the reproductive axis GnRH must be delivered in a pulsatile mode [109].…”
Section: Effects Of Kisspeptin Administration In Subjects With Reprodmentioning
confidence: 94%
See 1 more Smart Citation
“…4 In women with functional hypothalamic amenorrhea, the reactivation of GnRH/LH pulsatility by kisspeptin administration suggests that exogenous kisspeptin enters the central nervous system somehow crossing the blood-brain barrier. 5 Studies in energy-depleted animals with hypogonadotropic hypogonadism have reported a reduction in hypothalamic kisspeptin mRNA as well as in circulating LH levels. 2 To what extent hypothalamic mRNA changes due to undernutrition translate into alterations of kisspeptin release in the circulation remains as yet unknown.…”
Section: Introductionmentioning
confidence: 99%